A COMPARATIVE STUDY OF THE EFFECTS OF PRODUCT AND SERVICE QUALITY ON CUSTOMER SATISFACTION IN FAST FOOD RESTAURANTS: THE CASES OF BURGER KING AND KFC - Dari, Chimgee; Tsegmed, Tsevelmaa; Bat-Erdene, Dulguun; Odbayar, Nominzaya; Buyanjargal, Tsagaan-Erdene (Journal of Business and Innovation (Бизнес & Инноваци), 2026)
This study aims to examine the impact of product and service quality on customer satisfaction and loyalty in Burger King and KFC fast-food restaurants in Ulaanbaatar, Mongolia. A total of n = 200 respondents were surveyed, and the data were analyzed using descriptive statistics, correlation analysis, independent samples t-test, ANOVA, and multiple regression analysis. The results indicate that Burger King performs significantly better than KFC across key indicators (p < .05). Food quality was identified as the strongest predictor of customer satisfaction (β = .331, p < .05), followed by service quality, while price showed no statistically significant effect. These findings highlight the importance of maintaining high food quality and improving service performance.